2021
DOI: 10.9755/ejfa.2021.v33.i1.2356
|View full text |Cite
|
Sign up to set email alerts
|

Maize (Zea mays L.) landraces classified by drought stress tolerance at the seedling stage

Abstract: Drought is the main limiting factor for maize production, and climate change can aggravate this water scarcity. One way to mitigate this problem is to plant drought tolerance maize genotypes. In landrace maize grown under rainfed conditions there are drought-adapted genotypes, which can be used in breeding programs for drought tolerance. The objective of this study was to evaluate the effect of an early water deficit on the seedling growth of 41 maize landraces from Nuevo León, Mexico, plus seven varieties, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Line-1 (617.2; 584.2 and 0.69), Line-12 (608.7; 586.5 and 0.69) and Line-13 (611.7; 590.5 and 0,70) showed more higher value of MP, GMP and STI. Sayyah et al (2012), Karmani et al (2017 and Poudel et al (2021) reported the similar results and suggested selection based Hernandez et al, 2021). Decreasing yield in low water levels indicates that water is a limiting factor in experiment (Soares et al, 2021).…”
Section: Resultsmentioning
confidence: 71%
“…Line-1 (617.2; 584.2 and 0.69), Line-12 (608.7; 586.5 and 0.69) and Line-13 (611.7; 590.5 and 0,70) showed more higher value of MP, GMP and STI. Sayyah et al (2012), Karmani et al (2017 and Poudel et al (2021) reported the similar results and suggested selection based Hernandez et al, 2021). Decreasing yield in low water levels indicates that water is a limiting factor in experiment (Soares et al, 2021).…”
Section: Resultsmentioning
confidence: 71%
“…Most importanly, this is the first study to investigate effects of the induced passive heating in seedling emergence, initial growth and chlorophyll fluorescence of native seedling genotypes of maize taking account the three agro-ecological zones of the state of San Luis Potosí. Taking into account that Hernández et al (2021) reported that a solid start to the plant cycle (seedling stage) is critical for achieving a good end performance and a high grain yield. However, high seedling performance alone is insufficient to ensure a good grain production at the conclusion of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of maize lines by Chen et al. (2016) and Gonzalez-Hernandez et al. (2021) emphasize that the recovery phase influenced the final plant biomass more than the drought phase.…”
Section: Ideotypes and Geneticsmentioning
confidence: 99%
“…comparable to well-watered conditions), e.g., decrease ABA level, and restored fine roots through root regrowth ( Lauenroth et al., 1987 ; Luo, 2010 ; Fang and Xiong, 2015 ; Maurel and Nacry, 2020 ). Although both drought resistance and post-drought recovery are key determinants of plant growth, some recent studies suggest that recovery may play a more significant role in plant drought adaptation than drought resistance itself ( Chen et al., 2016 ; Gonzalez-Hernandez et al., 2021 ). Thus, to increase plant resistance and resilience [For definitions see ( Enright et al., 2014 ; Hoover et al., 2021 )], and maximize plant production, understanding root plasticity during both drought and recovery is necessary ( Vilonen et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%